Sequential randomised and double blind trial of promethazine prophylaxis against early anaphylactic reactions to antivenom for bothrops snake bites - Fan, H; Marcopito, L; Cardoso, J; Franca, F; Malaque, C; Ferrari, R; Theakston, R; Warrell, D (1999)
Objective. To investigate the efficacy of the H1 antihistamine promethazine against early anaphylactic reactions to antivenom. Design. Sequential randomised, double-blind, placebo controlled trial. Setting. Public hospital in a venom research institute, Sao Paulo, Brazil. Participants. 101 patients requiring antivenom treatment after being bitten by bothrops snakes. Intervention. Intramuscular injection of promethazine (25 mg for adults and 0.5/kg for children) or placebo given 15-20 min before starting intravenous infusion of antivenom. Main outcome measures. Incidence and severity of anaphylactic reaction occurring within 24 hours after antivenom. Results. Reactions occurred in 12 of 49 patients treated with promethazine (24%) and in 13 of 52 given placebo (25%); most were mild or moderate. Continuous sequential analysis indicated that the study could be interrupted at the 22nd united pair, without preference for promethazine or placebo. Conclusion. Prophylaxis with promethazine does not prevent early reactions. Patients should be observed carefully during antivenom infusion and the subsequent few hours.